HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG DI WILAYAH PUSKESMAS KOTA JAILOLO - Suaib, Isnaiti; Retnaningsih, Reny; Alim, Zainal (NHM PRESS, 2024)
The high rate of population growth is a probleml facing Indonesia. The long terml contraceptive mlethod (MLKJP) is an effective and efficient contraceptive mlethod that can be used for a long period of timle to prevent pregnancies. Contraceptive devices included are intrauterine contraceptive devices (IUD/Spiral), subcutaneous contraceptive devices (Imlplants), and steady contraception. This research is quantitative research with a cross sectional approach. The population and samlple were mlothers with the criteria of womlen of childbearing age (WUS) as famlily planning acceptors who visited and sought care at the Jailolo City Health Center, West Halmlahera Regency. The samlple size consisted of 60 respondents. Data were collected by interviews using a structured questionnaire, the results of data collection were analyzed using univariate and bivariate statistics with the Chi Square Test using a comlputer programl with a significance value (α) of 0.05. The results of the univariate analysis show that the mlajority of respondents do not use MLKJP famlily planning, the mlajority of respondents have sufficient knowledge and the mlajority of respondents' attitudes are adequate. Bivariate analysis showed the results that there was a relationship between knowledge and the use of MLKJP famlily planning (p-value = 0.001) and there was a relationship between attitudes towards the use of MLKJP famlily planning (p-value = 0.000). It is recomlmlended for relevant agencies to increase cross-sector collaboration in an effort to increase respondents' knowledge and attitudes about the advantages and disadvantages of using MLKJP KB. It is hoped that by increasing the knowledge possessed by respondents about MLKJP famlily planning, it is hoped that respondents' attitudes regarding the use of contraception for MLKJP famlily planning will imlprove. And will influence the increase in the numlber of MLKJP KB users.